The Florida Bull Test 2015-2016 - Carla D. Sanford; Graham Cliff Lamb; Nicolas DiLorenzo (EDIS)
The 16th annual Florida Bull Test Sale was held on January 16, 2016 at the conclusion of the 2015–2016 Florida Bull Test. The test evaluated the performance potential and breeding soundness of bulls consigned to the program at the UF/IFAS North Florida Research and Education Center (NFREC). This 10-page fact sheet covers the test procedures, assessment of feed efficiency, general policies and procedures, health requirements, test results, and sale summary. Written by Carla D. Sanford, G. Cliff Lamb, and Nicolas DiLorenzo, and published by the UF Department of Animal Sciences, November 2016.http://edis.ifas.ufl.edu/an328